(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
Persuasive interface designs are gaining a lot of importance in directing user behavior on digital platforms. While many of th tactics which forms part of the interface are important & also within the legal boundaries, other design practices—known as “dark patterns”—cross ethical boundaries and are used purposively for deceiving the consumers through various social media channels. Three main aspects are examined in this conceptual paper: (1) the meaning and types of dark patterns; (2) the extent to which consumers are aware of these trends when using online platforms; and (3) the level of awareness among users regarding the legal protections and regulatory framework available against manipulative dark patterns used digitally . The paper focused on how consumers are actually aware of the various types of dark patterns used on the digital platforms.The research paper is beneficial for the consumers as it creates awareness among them, for policymakers on how to create a user friendly digital user interface for digital literacy.